If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -3x = -12 + 8x Solving 10 + -3x = -12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 10 + -3x + -8x = -12 + 8x + -8x Combine like terms: -3x + -8x = -11x 10 + -11x = -12 + 8x + -8x Combine like terms: 8x + -8x = 0 10 + -11x = -12 + 0 10 + -11x = -12 Add '-10' to each side of the equation. 10 + -10 + -11x = -12 + -10 Combine like terms: 10 + -10 = 0 0 + -11x = -12 + -10 -11x = -12 + -10 Combine like terms: -12 + -10 = -22 -11x = -22 Divide each side by '-11'. x = 2 Simplifying x = 2
| 3*-1+y=5 | | 2(3-r)=-70 | | 3*1+y=5 | | 150+50x=40+50x | | 2(3-r)=70 | | 3*0+y=5 | | 2(3z-2)-2(5-2z)=-4 | | 3t-t=8 | | 11+2x=17+x | | -39t+7t^2-18=0 | | -6-x=-3x+2 | | 123-a=97 | | 7+3c=91 | | -15=-6b+3b | | 100+12x=50+30x | | -6+x/6=-5 | | 7v-4v=15 | | 16x^2+16x-5/4x-1 | | W+h=-8 | | 5-6r-2r=-3 | | 2*2-y=1 | | 4x-4/3 | | 2*1-y=1 | | 4+3t=32+t | | 4n-2+3n=-16 | | 3(p+4)=12 | | (x+3)/(x+5)+(6)/(x^2+3x-10) | | 50=-16t^2+32t+50 | | 1/2-7/8 | | 0=x-2+4 | | 10x+27y-9=360 | | 10=-3p+p |